Design of Automatic drug infusion system for mean arterial blood pressure control using cuckoo search algorithm - V., Gomathy; R., Gopi; M., Rajaram; E. , Ahila Devi; E. , Anna Devi (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents the optimal control design for an automatic drug infusion system to control the physiological state, such as mean arterial pressure (MAP), by manipulating sodium nitroprusside (SNP). The design of a multi-delivery drug system is very difficult to design due to the patients’ sensitivity and dynamics. This paper presents the design procedure for an optimal controller for a drug delivery system using the Cuckoo search algorithm. The simulation result shows the superiority of the proposed controller design.